1995
DOI: 10.1016/0896-6273(95)90092-6
|View full text |Cite
|
Sign up to set email alerts
|

Fear conditioning enhances short-latency auditory responses of lateral amygdala neurons: Parallel recordings in the freely behaving rat

Abstract: The lateral nucleus of the amygdala (LA) is the first site in the amygdala where the plasticity underlying fear conditioning could occur. We simultaneously recorded from multiple LA neurons in freely moving rats during fear conditioning trials in which tones were paired with foot shocks. Conditioning significantly increased the magnitude of tone-elicited responses (often within the first several trials), converted unresponsive cells into tone-responsive ones, and altered functional couplings between LA neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
595
5
5

Year Published

1996
1996
2007
2007

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 732 publications
(660 citation statements)
references
References 55 publications
55
595
5
5
Order By: Relevance
“…This is comparable to the percentage of correlated BLA neurons recorded in prior conditioning studies (Muramoto et al, 1993;Quirk et al, 1995). Twenty-eight neurons showed correlates that centered on reward acquisition at the 1 2 3 4…”
Section: Cell Classificationsupporting
confidence: 79%
“…This is comparable to the percentage of correlated BLA neurons recorded in prior conditioning studies (Muramoto et al, 1993;Quirk et al, 1995). Twenty-eight neurons showed correlates that centered on reward acquisition at the 1 2 3 4…”
Section: Cell Classificationsupporting
confidence: 79%
“…As synaptic plasticity in the LA is thought to underlie fear memories (Quirk et al, 1995;Collins and Pare, 2000;Repa et al, 2001;Bauer et al, 2002), we also tested for LTP in VPA-treated rats. We found that the potentiation caused by a classical pairing protocol with an extracellular electrode placed just medial to the LA was significantly increased in treated rats (t 12 ¼ 3.12 p ¼ 0.009; n ¼ 15 for control, 10 for treated; Figure 4c).…”
Section: In Vitro Slice Electrophysiology In the Basolateral Amygdalamentioning
confidence: 99%
“…Synaptic plasticity is also boosted suggesting that the amygdala turned hyperplastic following a single exposure of the embryo to VPA. Considering that LTP in the basolateral amygdala is thought to be the key cellular mechanism underlying fear memory formation (Quirk et al, 1995;Rogan et al, 1997;Collins and Pare, 2000;Repa et al, 2001;Bauer et al, 2002), hyperreactivity and hyperplasticity are strong candidates mediating the enhanced and overgeneralized fear memories in the VPA-treated rats.…”
Section: A Novel Role Suggested For the Amygdala In Autismmentioning
confidence: 99%
“…The association formed between the CS and US can elicit a conditioned fear response (CR) when the CS is presented alone. In rodents the most readily observable CRs include freezing, response suppression (Quirk et al, 1995;Killcross et al, 1997;Fendt and Fanselow, 1999;Gewirtz and Davis, 2000;LeDoux, 2000), and autonomic changes such as tachycardia (Young and Leaton, 1994;Nijsen et al, 1998) and increased body temperature (Noble and Delini-Stula, 1976). Although the neural and molecular mechanisms underlying the formation of CS-US associations are well established (for reviews, see Davis, 2000;Rodrigues et al, 2004), those mechanisms that mediate the suppression of an established fear response in extinction are less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Quirk et al (1995) reported that the acquisition of learned fear was associated with LTP-like increases in firing in neurons in the lateral amygdala. However, when these animals were subjected to extinction training in the same session, these neurons exhibited a gradual decrease in firing in response to CS presentations.…”
Section: Introductionmentioning
confidence: 99%